Fresh tracks in the forest: assessing incipient payments for environmental services initiatives in Bolivia - Robertson, N.; Wunder, Sven (Center for International Forestry Research, 2005)
Payments for Environmental Services (PES) are being considered worldwide with great interest and expectation. Proposals to create agreements in which beneficiaries of environmental services pay landowners directly for the provision or protection of these services are innovative and promising. But what real PES experiences are actually out there? This work assesses a range of PES or PES-type experiences in one country, Bolivia, in the fields of carbon sequestration, protection of watershed services, biodiversity and aesthetic landscape values. The report concludes that while none of the generally young initiatives adhere fully to the principle of PES as developed in the theoretical literature, many experiment with some of the relevant PES mechanisms. Protection of watersheds and landscape values are the most common types, though the implementing intermediaries often have underlying biodiversity-protection goals. Main obstacles to PES implementation include ideological resistance against the PES concept, the difficulty of building trust between buyers and sellers, and limited willingness to pay on behalf of service users. During their relatively short lifetime, basically all initiatives had been successful in making service sellers (PES recipients) better off in economic terms, while the effectiveness in achieving environmental objectives and securing positive social impacts so far remained more variable. In some cases, redesigning these initiatives to bring them closer to the full PES principles could also enable them to more effectively achieve positive environmental and livelihood outcomes.